EFEKTIVITAS BELAJAR DARING SISWA SD BANDA ACEH-ACEH BESAR PADA MASA PANDEMI COVID 19 - Zaki Al Fuad (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2020)
At the end of 2019, the world was shocked by the emergence of a deadly virus; (Coronavirus Disease 19 (COVID 19). Since its emergence, the Indonesian government issued a policy set out in Government Regulation Number 21 of 2020 concerning Large Scale Social Restrictions. One of the policies is to stop learning activities at school, that is replaced by online learning at home. This regulation has been stated in the Ministry of Education and Culture Circular Letter number 15 of 2020;